Take it from the Top: How Intensity of TMT Joint Problem Solving and Levels of Interdependence Influence Quality of Strategy Implementation Coordination and Firm Performance. (3rd June 2022) - Mistry, Sal; Kirkman, Bradley L.; Hitt, Michael A.; Barrick, Murray R.
Abstract: Despite the belief that strategy implementation begins at the very top of a firm, there remains an inadequate understanding about top management teams' (TMTs) involvement in the strategy implementation process. Building upon and extending strategic leadership theory, we develop and empirically test a theoretical model of the interactive effects of the intensity of TMT joint problem solving and level of TMT interdependence on quality of TMT strategy implementation coordination and firm performance. Using data collected from TMTs in 83 firms, our results show that the: intensity of TMT joint problem solving is positively related to quality of TMT strategy implementation coordination; interaction between the intensity of TMT joint problem solving and the level of TMT interdependence attenuates the positive influence of each on quality of TMT strategy implementation coordination, demonstrating a substitution effect; and, quality of TMT strategy implementation coordination mediates the relationship between the interaction and firm performance.